Influence of Asian and Western U.S. Urban Areas and Fires on the Atmospheric Transport of PAHs, PCBs, and FTOHs in the Western U.S - Primbs, Toby (2008)
Atmospheric measurements of semivolatile organic compounds (SOCs) were made at Mt. Bachelor Observatory (MBO), located in Oregon’s Cascade Range, to understand the trans-Pacific and regional transport of SOCs from urban areas. High volume air sampling (~644 m(3) for 24 hour periods) of both the gas and particulate phases was conducted from the 19(th) of April 2004 to the 13(th) of May 2006 (n=69); including NASA’s INTEX-B campaign in spring 2006 (n= 34 of 69). Air mass back trajectories were calculated and used to calculate source region impact factors (SRIFs), the percentage of time the sampled air mass resided in a given source region. Particulate-phase polycyclic aromatic hydrocarbon (PAH) concentrations at MBO increased with the percentage of air mass time in Asia and, in conjunction with other data, provided strong evidence that particulate-phase PAHs are emitted from Asia and undergo trans-Pacific atmospheric transport to North America. Gas-phase PAH and fluorotelomer alcohol (FTOH) concentrations significantly increased with the percentage of air mass time in California’s urban areas, while retene and polychlorinated biphenyl (PCB) concentrations increased with the percentage of air mass time in Oregon and during regional fire events. In addition, Σgas-phase PAH, retene, and levoglucosan concentrations were significantly correlated (p-value < 0.001) with ΣPCB concentrations, suggesting increased atmospheric PCB concentrations were associated with fires due to the volatilization of stored PCBs from soil and vegetation.